Tools for living : a sourcebook of iconic designs for the home - Fiell, Charlotte, 1965-; Fiell, Peter (London Fiell, 2010)
'Tools For Living' is a book all about 'ultimates' - the ultimate things designed for the home - from chef knives and pots and pans, to door handles and bathroom taps, to home-office furniture and garden tools.
Kitchenware Tableware Furniture Lighting Bathroom Other Children
Includes index.
Text in English, French and German.
Keywords: Industrial design -- History -- 21st century -- Catalogs; Furniture design -- History -- 21st century -- Catalogs